The Sulfate-Reducing Microbial Communities and Meta-Analysis of Their Occurrence during Diseases of Small-Large Intestine Axis - Kushkevych, Ivan; Leščanová, Oľga; Dordević, Dani; Jančíková, Simona; Hošek, Jan; Vítězová, Monika; Buňková, Leona; Drago, Lorenzo (Journal of clinical medicine, 2019)
Sulfate-reducing bacteria (SRB) are often isolated from animals and people with ulcerative colitis and can be involved in the IBD development in the gut-intestine axis. The background of the research consisted of obtaining mixed cultures of SRB communities from healthy mice and mice with colitis, finding variation in the distribution of their morphology, to determine pH and temperature range tolerance and their possible production of hydrogen sulfide in the small-large intestinal environment. The methods: Microscopic techniques, biochemical, microbiological, and biophysical methods, and statistical processing of the results were used. The results: Variation in the distribution of sulfate-reducing microbial communities were detected. Mixed cultures from mice with ulcerative colitis had 1.39 times higher production of H2S in comparison with samples from healthy mice. The species of Desulfovibrio genus play an important role in diseases of the small-large intestine axis. Meta-analysis was also used for the observation about an SRB occurrence in healthy and not healthy individuals and the same as their metabolic processes. Conclusions: This finding is important for its possible correlation with inflammation of the intestine, where the present of SRB in high concentration plays a major part. It can be a good possible indicator of the occurrence of IBD.
Keywords: colitis; bowel disease; small–large intestine axis; sulfate reduction; hydrogen sulfide